Managerial thinking in neonatal care: a qualitative study of place of care decision-making for preterm babies born at 27–31 weeks gestation in England. Issue 6 (27th June 2022) - Cupit, Caroline; Paton, Alexis; Boyle, Elaine; Pillay, Thillagavathie; Armstrong, Natalie
Abstract : Objectives: Preterm babies born between 27 and 31 weeks of gestation in England are usually born and cared for in either a neonatal intensive care unit or a local neonatal unit—with such units forming part of Operational Delivery Networks. As part of a national project seeking to optimise service delivery for this group of babies (OPTI-PREM), we undertook qualitative research to better understand how decisions about place of birth and care are made and operationalised. Design: Qualitative analysis of ethnographic observation data in neonatal units and semi-structured interviews with neonatal staff. Setting: Six neonatal units across two neonatal networks in England. Two were neonatal intensive care units and four were local neonatal units. Participants: Clinical staff (n=15) working in neonatal units, and people present in neonatal units during periods of observation. Results: In the context of real-world neonatal practice, with multiple (and rapidly-evolving) uncertainties relating to mothers, babies and unit/network capacity, 'best place of care' protocols were only one element of much more complex decision-making processes. Staff often made judgements from a less-than-ideal starting point, and were forced to respond to evolving clinical and organisational factors. In particular, we report that managerial considerations relating to demand and capacity organised decision-making; demand and capacity management was time-consuming and generated various pressures on families, and tensions between staff. Conclusions: Researchers and policymakers should take account of the organisational context within which place of care decisions are made. The dominance of demand and capacity management considerations is likely to limit the impact of other improvement interventions, such as initiatives to integrate families into the neonatal care provision. Demand and capacity management is an important element of neonatal care that may be overlooked, but significantly organises how care is delivered.